Out of time - Marsden, John, 1950- (New York : Tor, 2007)
James, a strange, silent boy, makes the acquaintance of old Mr. Woodford, a physicist who constructs a mysterious black box, but when the box comes into the boy's possession, it draws him into a magical and dangerous world, in and out of time.
"A Tom Doherty Associates Book."
Keywords: Time travel -- Juvenile fiction; Science fiction